Evaluasi Kuantitatif Massa Batuan Berdasarkan Klasifikasi Geomekanik Dan Geological Strength Index Pada Penambangan Batugamping Dolomit, Studi Kasus Kecamatan Semanding, Kabupaten Tuban, Propinsi JawaTimur - , Helmi Dwiyuniarto ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The dolomitic limestones on study area are small scale mining activity which operates with simple equipments. These dolomitic limestone mining study areas are located on Kecamatan Semanding, Kabupaten Tuban, Propinsi Jawa Timur which geographically are located on 111Â° 59â â 112Â° 7â E longitude dan 6Â° 58ââ 7Â° 2â S latitude. All of the 77 dolomitic limestone mining areas are distributed just on 3 villages, Desa Bektiharjo, Desa Prunggahan Kulon and Desa Jadi. The dolomitic limestones on study area are operates with simple surface mining methods results vertical steep slopes, or by underground mining methods results caves. According with that, needs an evaluation and recomendation to determined the condition of dolomitic limestone mining based on Geomechanical Classification (RMR/Rock Mass Rating) and Geological Strength Index (GSI), and also for define the correlations between both rockmass classifications in the study areas. From field observation data, laboratory analyzed, evaluation criteria and so many rock mass classification parameter calculation, even with qualitative or quantitative methods that found in 77 dolomitic limestone mines location at Kecamatan Semanding, results GSIâs grades for rock mass that contain discontinuities are range between 61 â 79 (GSI = 100, for intact rockmass) with cohesion (câ) variations between 0,03 â 0,52 Mpa and friction angle (Ï') 42,69 â 55,90Â°. This results shows that the study areas contains soft to hard rock masses with no major structural disturbing. According to kinematic analysis from surface mining of the dolomitic limestone that contain discontinuities, there are 3 locations which have potential instability (plane failures), OC-17, OC-32 and OC 73. After analyzed with slope stability analysis, we find those slopes are completely stable. RMR89âs grades (corrected RMR) for underground mining rock mass that contain discontinuities are range between 51 â 69 (RMRâs class III â II). On RMR class II, can be set wire mesh occasionally and complete support 20 m from face. For the next excavation process, preferably to make narrower span, around 2 â 4 meter for no support tunnel require. On RMR class III, can be set wire mesh in specify locations and complete support 10 m from face. For the next excavation process, preferable to make narrower span, around 2 â 3 meter for no support tunnel required with Top-Heading and Bench excavations method. SMRâs grades for surface mining rock mass that contain discontinuities are range between 15,80 â 76,03 (SMRâs class V â II). On SMR class II and III, can be apply slopebench mining method to decrease steepness angle into the safe slope. On SMR class IV and V, suggest to re-excavate from another slope face side From GSI and RMR89 (adjustment to dry basic RMR) grades, we can find relation between GSI and RMR for dolomitic limestone mining on semanding area is GSI = 0,52 RMR + 34,30 , with range of RMR89 (adjustment to dry basic RMR) = 63 â 79 and GSI = 66 â 79.